Digital trailblazer : essential lessons to jumpstart transformation and accelerate your technology leadership - Sacolick, Isaac (John Wiley & Sons, Inc., 2022)
"Several years into their careers, technologists, product managers, and data scientists begin thinking about leadership roles. They may ask, "What's it like to be a CIO, CTO, or Chief Digital or Data Officer? What should I learn, and what types of roles should I seek to gain the most relevant experience? To get started, what leadership skills do I need to be a Director or a VP? If I get a more senior role, then how should I develop relationships with colleagues, executives, and board members?" Many of these high potentials seek greater responsibilities in established organizations. They must drive transformation into digital businesses where developing customer experiences, analytics, and digital workflows enable competitive differentiation. Others might consider joining startups, but they also recognize a need to broaden their transformation skills and shift from getting things done to driving business outcomes. More importantly, emerging leaders want to know how to broaden their leadership skills and better understand how to succeed in driving transformative changes. The author believes that the best way to learn aspects of leadership and transformation is from stories. He has seen it every time he keynotes a conference and goes into storytelling mode. The audience's eyes lift off their cellphones and listen. People understand and remember the lessons through relevant stories. In this book, the author shares some of his best stories that helped him learn and understand transformative leadership. Each chapter has intertwining stories from across my career crafted in a stream of thought writing style. Each chapter concludes with five lessons learned, and with some chapters, lessons learned by other leaders who contribute to the book"--